The Circulatory and Metabolic Responses to Hypoxia in Humans - With Special Reference to Adipose Tissue Physiology and Obesity - Heinonen IHA; Boushel R; Kalliokoski KK (FRONTIERS MEDIA SA, 2022)
Adipose tissue metabolism and circulation play an important role in human health. It is well-known that adipose tissue mass is increased in response to excess caloric intake leading to obesity and further to local hypoxia and inflammatory signaling. Acute exercise increases blood supply to adipose tissue and mobilization of fat stores for energy. However, acute exercise during systemic hypoxia reduces subcutaneous blood flow in healthy young subjects, but the response in overweight or obese subjects remains to be investigated. Emerging evidence also indicates that exercise training during hypoxic exposure may provide additive benefits with respect to many traditional cardiovascular risk factors as compared to exercise performed in normoxia, but unfavorable effects of hypoxia have also been documented. These topics will be covered in this brief review dealing with hypoxia and adipose tissue physiology.